2014
DOI: 10.1002/poc.3311
|View full text |Cite
|
Sign up to set email alerts
|

Electronic descriptors for analytical use of the benzidine‐based compounds and the mechanism of oxidative coupling of anilines

Abstract: A number of hybrid exchange-correlation functionals, namely, B3LYP, BMK, M06-2X, PBE0, CAM-B3LYP, BH&HLYP, and HSE06, have been employed to calculate the electronic spectra of a series of the N,N′-derivatives of benzidine, their radical cations, and dications; the results are compared with available experimental data. In most cases studied, the timedependent density functional theory results based on the CAM-B3LYP and BMK functionals indicate a better agreement with the experimental absorption bands in the UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…This mechanism is in line with one discussed by Bondarchuk and Minaev for the oxidative coupling of anilines [29]. More generally, it is related to the oxidative dimerization of arylamines to benzidines with Cu 2+ or iron oxidants [22, 30, 31].…”
Section: Resultssupporting
confidence: 79%
“…This mechanism is in line with one discussed by Bondarchuk and Minaev for the oxidative coupling of anilines [29]. More generally, it is related to the oxidative dimerization of arylamines to benzidines with Cu 2+ or iron oxidants [22, 30, 31].…”
Section: Resultssupporting
confidence: 79%
“…Note that the resonance structure of the Bph 2is the same as for the previously calculated biphenyl and benzidine dication. 27,28 The QTAIM properties of these contact ionic pair are listed in Table S5 in ESI. Calculations of the electronic spectra of the aforementioned associates are illustrated in Fig.…”
Section: Njc Articlementioning
confidence: 99%
“…Recently, we have found that a number of local Quantum Theory of Atoms in Molecules properties are convenient for the structure‐activity description in benzidine and its singly and doubly oxidized forms . Being calculated in the bond critical points (BCP), these can clarify the electron distribution and, consequently, the reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have found that a number of local Quantum Theory of Atoms in Molecules properties are convenient for the structure-activity description in benzidine and its singly and doubly oxidized forms. [49,50] Being calculated in the bond critical points (BCP), these can clarify the electron distribution and, consequently, the reactivity. Among these AIM quantities, we have used the electron density ρ(r), its Laplacian ∇ 2 ρ(r), energy densities h e (r), g(r), and v(r), [51] bond ellipticity ε(r), [51] average local ionization energy Ī(r), [52] localized orbital locator, [53] and electron localization function (ELF).…”
Section: Quantum-chemical Calculationsmentioning
confidence: 99%